2008
DOI: 10.1021/ef800695k
|View full text |Cite
|
Sign up to set email alerts
|

Studies of NO−Char Reaction Kinetics Obtained from Drop-Tube Furnace and Thermogravimetric Experiments

Abstract: Four coal chars were prepared in a flat flame flow reactor (FFR), which can simulate the temperature and gas composition of a real pulverized coal combustion environment. The pore structure of chars was measured by mercury porosimetry and nitrogen adsorption, and the Hg and Brunauer-Emmett-Teller (BET) surface areas were obtained. The kinetics of NO-char was studied in a drop-tube furnace (DTF) and thermogravimetric analyzer (TGA). In the TGA experiments, the random pore model (RPM) was applied to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…32,34 The CaO surface area increases with the burnout level because of an increase in the CaO content per gram of char as the carbonaceous mass burns away. These results indicate that the CaO surface area is a more reliable basis than the BET surface area for correlating the burnout level with surface area measurements, which agrees with Sun et al 45 Effect of the Method B Burnout Level on the NO− Char Rate Constant. Figures 4 and 5 show the variations of NO−char reaction rates with the char burnout level obtained under method B conditions for biomass, graphite, and six coal chars.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…32,34 The CaO surface area increases with the burnout level because of an increase in the CaO content per gram of char as the carbonaceous mass burns away. These results indicate that the CaO surface area is a more reliable basis than the BET surface area for correlating the burnout level with surface area measurements, which agrees with Sun et al 45 Effect of the Method B Burnout Level on the NO− Char Rate Constant. Figures 4 and 5 show the variations of NO−char reaction rates with the char burnout level obtained under method B conditions for biomass, graphite, and six coal chars.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…However, there are a number of studies indicating that the heterogeneous reduction of NO using biomass char is also noteworthy (Dong et al, 2007(Dong et al, , 2009aGarijo et al, 2003;Lin et al, 2010;Sun et al, 2009;Yin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous researches on the reaction between coal char and NO are conducted at a temperature below 1173 K, which is widely recognized as the transition temperature from dynamic-control region to diffusion-control region (Aarna and Suuberg, 1997;Sun et al, 2009). However, there is no widely recognized transition temperature for the reaction between biomass char and NO.…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study, 41 the char-NO reaction is found to be first-order with respect to NO. The calculation method of intrinsic reactivity of char-NO reaction R 4 can be found elsewhere 42 using the classical Thiele analysis. The Arrhenius plot of R 4 is obtained by linear fitting as shown in Figure 5.…”
Section: Energy and Fuelsmentioning
confidence: 99%